PENGARUH GAYA KEPEMIIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI - Zakiyya Tunnufus; Reksa Dwi Sucipta (The Asia Pacific Journal Of Management Studies, 2017)
Human resources is an important factor in achieving the objectives for private companies and government agencies. In fact, the performance of employees is often up and down, to that agency should be able to understand the ups and downs because of existing employee performance. Whether or not the employee's performance is strongly influenced how a leader influence and motivate the employees in order to perform a variety of jobs as expected.In this study the authors using Statistical Product and Service Solution SPSS Version20. Results of research on leadership style obtained t 4.201 with sig level. 0,000, because thitung greater than ttable or taccount 4.201 ≥ 2.042 ttabel then Ho is rejected and Ha accepted and it can be concluded that there are significant leadership style on performance. So also the motivation variable obtained t 3.085 with sig level. 0,000, because thitung greater than ttable or taccount 3.085 ≥ 2.042 ttabel then Ho is rejected and Ha accepted and concluded that there are motivational influence on performance. While From the results of test calculations f or anova test results obtained Fcount ≥ 74.858 Ftable 3:33 with a significant level of 0.000. It can be  concluded that there is significant influence between leadership  style (X1), and motivation (X2) with the same (stimultant) on employee performance (Y) and vice versa. The results of the correlation coefficient value relationship "Very Strong" and based on the R-square is found that variables can affect 83.8% while the remaining 16.2% is explained by other variables with multiple linear regression equation Y = 0,255 + 0.597X1+0.396X2.Based on the above results it can be seen that the style of leadership and motivation positive and significant impact on the performance of employees in the office and village authorities Empowerment Board (BPMPD) Lebak.